2005
DOI: 10.1074/jbc.m414530200
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Induction by Prostaglandin E2 in Human Airway Smooth Muscle Cells Is Mediated by E Prostanoid EP2/EP4 Receptors and SP-1 Transcription Factor Binding Sites

Abstract: Prostaglandin E 2 (PGE 2 ) can increase vascular endothelial growth factor A (VEGF-A) production but the mechanisms involved are unclear. Here we characterized the transcriptional mechanisms involved in human airway smooth muscle cells (HASMC). PGE 2 increased VEGF-A mRNA and protein but not mRNA stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 44 publications
(46 reference statements)
7
63
1
Order By: Relevance
“…Finally, it has been shown that EP2 and VEGF receptor can cooperate in regulating endothelial cell motility (Bradbury et al, 2005;Chang et al, 2005). In this regard, we show here that stimulation with PGE 2 or angiogenic factors (i.e.…”
Section: Discussionsupporting
confidence: 63%
“…Finally, it has been shown that EP2 and VEGF receptor can cooperate in regulating endothelial cell motility (Bradbury et al, 2005;Chang et al, 2005). In this regard, we show here that stimulation with PGE 2 or angiogenic factors (i.e.…”
Section: Discussionsupporting
confidence: 63%
“…We show that the CCN1 promoter is activated by either cAMP or following treatment with PGE2, which elevates the internal pool of cAMP in the cells (37). PGE2 is known to promote tumor growth, angiogenesis, and cell migration and to up-regulate VEGF (43). Interestingly, PGE2 was recently found to be activated by CCN1 (30).…”
Section: Creb-mediated Regulation Of Ccn1 At Hypoxia Mol Cancer Res 2mentioning
confidence: 83%
“…Sp1 is a ubiquitously expressed transcription factor that recognizes GC-rich sequences present in the regulatory sequences of numerous housekeeping genes and those genes that are involved in growth regulation and cancer (34,45). The transcription factor Sp1-response element is present in the promoter region of various genes, including uPA, MMP-9, and VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cell-derived VEGF binds to its specific receptors and regulates tumor progression through neovascularization via autocrine and paracrine pathways (43,44). Recent evidence suggested that the VEGF promoter contains an Sp1-response element (45). However, the role of Lck and Syk in H/R-induced VEGF expression in breast cancer is not defined clearly.…”
mentioning
confidence: 99%